ANALYZING ICT-BASED SYLLABUS INTEGRATED WITH 21ST CENTURY SKILLS FOR FRENCH WRITING SKILLS - Dian Savitri; Sri Harini Ekowati; Wahyu Tri Widyastuti (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
The 21st century demands the integration of 21st century skills in the curriculum. Therefore, French Language Education Study Program at Univeritas Negeri Jakarta developed a syllabus for Production Ecrite (PE) course or writing skills from semester I to semester IV. The initial step of the research was to analyze the PE syllabi from French Language Education Study Program of UNJ and 4 ex-IKIP universities having French Language Education Study Programs, such as Universitas Negeri Yogyakarta, Universitas Pendidikan Indonesian, Universita Negeri Medan, and Universitas Negeri Semarang. The elements analyzed in the syllabi were the completeness of the RPS format for PE course and the analysis of the elements of the 21st century skills. The format of the RPS completeness refers to Permenristekdikti No. 44 of 2015, that an RPS must have an identity, learning outcomes, indicators, learning methods, time allocation, learning experience, and criteria / indicators of rating weigth. Meanwhile, the elements of 21th century skills were seen through the existence of 4C elements, namely critical thinking & problem solving, creative & innovation, collaboration, and communication. The results of the analysis showed that the RPSs were good since it referred to Permenristekdikti No. 44 of 2015. However, some RPSs were not integrated with the 21st century skills.